The impact of top-down policy changes on socioeconomic status of Orang Asli - Nurulaisyah Rosli, Roslina Ismail, Jumadil Saputra, (Opción, 2019)
This study is written to investigate the impact of top-down policy change on the socioeconomic status of Orang Asli. The study design is quantitative research through a survey questionnaire. Total 49 head of households were participated and collected using simple random sampling. The data were analysed using descriptive (e.g. frequency and percentage) and inferential statistical analyses and assisted by SPSS-23. The results showed that the household income of respondents do not significantly different based on their age and education levels. In other words, the top-down policy changes do not give a significant impact on increasing socioeconomic status of Orang Asli.